INCIDENCE OF DENGUE HEMORRHAGIC FEVER (DHF) IN SEMARANG COASTAL AREA: EPIDEMIOLOGY DESCRIPTIVE CASE AND BIONOMIC VECTOR - Martini, Martini (Indonesian Journal of Tropical and Infectious Disease, 2019)
North Semarang sub-district is located on the coast of the Java Sea. The coastal area is characterized by high salt content on both the ground and the water compare to other areas. The high salt content environment should have limited the breeding of Dengue Hemorrhagic Fever (DHF) vectors; yet, quite high incidents of DHF cases are reported taken place in North Semarang coastal area. The aim of this study was to describe the epidemiology of DHF incidence, characteristic of cases, and bionomics vector in the coastal area of North Semarang sub-district. This study was applied descriptive observational design to analyze samples consisting of 62 dengue cases and 184 houses. The research variables consisted of coordinate of DHF cases, water salinity, House Index (HI), Container Index (CI), and Aedes species. Data were processed using SPSS in a bivariate manner; while, mapping was analyzed spatially using ArcGIS 10.3. A total of 184 houses were surveyed and 55 cases of DHF were identified. Most cases occurred in 6 -16 year age group (47.3%), water salinity ranged from 2-3%, indicating that the water in the coastal area tended to be brackish water. The results of the Pearson Correlation test showed that there was no relationship between HI and Incidence Rate (IR) of DHF in North Semarang District. Aedes aegypti was identified in a positive container, otherwise Aedes albopictus was not found. DHF cases mostly occurred in school age groups, and were distributed in all villages near or far from the beach. DHF vector could breed in areas with little brackish water, so that dengue transmission might occur in this area.